Numerical Investigation of Cross Ventilation Flow in A Gable Roof Building with Asymmetric Opening Positions - Deka, Rupam; Das, Kalyan Kumar; Das, Dipankar (International Journal of Integrated Engineering, 2024)
Natural ventilation can be a suitable alternative to mechanical ventilation as it is cost-effective and environmentally friendly. Therefore, an effective design of the natural ventilation system is very crucial. In this work, an attempt has been made to investigate the impact of opening positions and roof pitch on the performance of wind-induced cross-ventilation in a gable roof building. Numerical simulations were carried out using the computational fluid dynamics (CFD) technique based on the steady Reynolds averaged Navier-Stokes equations (RANS) model. Six configurations with asymmetric openings on opposite facades were considered to evaluate the effect of opening positions. Further, for studying the influence of roof pitch on the flow properties, three roof pitches, viz. 3:10, 5:10 and 7.5:10 were considered. It is found that the configuration with a windward opening in the middle and a leeward opening at the bottom (Configuration D) has the highest flow rate. The configuration with a windward opening at the top and a leeward opening at the bottom (Configuration B) has the lowest flow rate. Furthermore, the investigation with different roof pitches reveals that buildings with lower roof pitches are more vulnerable to wind loading due to higher flow separation at the windward eave. The investigation concludes that the opening position and roof pitch significantly influences the indoor airflow characteristics thereby affecting the ventilation performance.